Chemoenzymatic Synthesis of Nonasulfated Tetrahyaluronan with a Paramagnetic Tag for Studying Its Complex with Interleukin‐10. Issue 16 (25th February 2016) - Köhling, Sebastian; Künze, Georg; Lemmnitzer, Katharina; Bermudez, Marcel; Wolber, Gerhard; Schiller, Jürgen; Huster, Daniel; Rademann, Jörg
Abstract: Implants and artificial biomaterials containing sulfated hyaluronans have been shown to improve the healing of injured skin and bones. It is hypothesized that these effects are mediated by the binding of sulfated glycosaminoglycans (GAGs) to growth factors and cytokines, resulting in the sequestering of proteins to the wound healing site and in modulated protein activity. Given that no direct synthetic access to sulfated oligohyaluronans has been available, little is known about their protein binding and the structure of the resulting protein complexes. Here, the chemoenzymatic preparation of oligohyaluronans on the gram scale is described. Oligohyaluronans are converted into anomeric azides at the reducing end, enabling the attachment of analytical labels through an anomeric ligation reaction. A nonasulfated tetrahyaluronan–ethylenediaminetetraacetic acid derivative has been produced and used as a paramagnetic tag for the elucidation of the complex of this ligand with interleukin‐10 using paramagnetic relaxation enhancement NMR analysis. The metal ion position is resolved with 1.0 Å, enabling a refined structural model of the complex. Abstract : Understanding the sulfation code? Sulfated hyaluronans exert numerous biological functions through carbohydrate–protein binding (see figure). A paramagnetic tag enables the elucidation of the binding site and structure of the complex through paramagnetic relaxation enhancement (PRE)‐NMR analysis.